Assessment of water quality based on biological indices of macrobenthos: a river under pressure from tourism activities - Asep Sahidin; Zahidah Zahidah; Herman Hamdani; Heti Herawati; Mochamad Candra Wirawan Arief; M. Suhaemi Syawal; Aiman Ibrahim; Roni Sewiko; Chitra Octavina (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2021)
Cijulang River is one of the leading ecotourism objects in Pangandaran, West Java Province, Indonesia. However, the river has a variety of activities that can increase the water pollution in the river such as Green Canyon cliffs tourism, ecotourism of mangrove conservation, housing, and industrial siting. Macrobenthos is one of the bio-indicators that can assess the rate of water pollution in rivers, especially their organic pollutants. Therefore, this research aims to determine water pollution status in Cijulang River Tourism by comparing various biotic indices. The study was conducted at four site sampling locations from upstream to downstream in the rainy season period and dry season period using different methods namely, line transect model, water quality assessment by biological indexing (diversity, species dominant, and family biotic), species deficit, and organic measurement. The research showed 5873 macrobenthos and divided into 27 species with an average abundance of 167 ind.m-2 and are mainly dominated by gastropod species Faunus ater (40%). They are extreme species that can live in high organic pollution and water salinity. This divided the research of quality water assessment of Cijulang River into three categories as follows: slightly polluted (score 36-46) at Green Canyon site, moderately polluted (score 50-60) at Boat Shelter and Muara Cijulang location, and highly polluted (score 66) at Nusawiru site.Keywords:RiverBio-indicatorOrganicAquatic pollution